Polycyclic Aromatic Hydrocarbons (PAHs) in “Yerba Mate” (Ilex paraguariensis) Fractions - García Londoño, Víctor Alonso (2018)
The aim of this study was to evaluate polycyclic aromatic hydrocarbons (PAHs) contamination, distribution, and toxicity in “yerba mate” fractions, and to propose actions to reduce its pollution. Sixteen PAHs were quantified using a recently developed methodology by HPLC-DAD/FLD, obtaining recoveries higher than 84.5% and relative standard deviation of individual compounds from 0.2% to 9.6%. The PAHs distribution was not normal. The Inverse Gaussian, Birnbaum-Saunders, Lognormal, Gamma, and Weibull were the models that best described benzo(a)pyrene and PAH4 distribution. The fraction that was significantly less contaminated was stem. Also, there was significant difference between leaf and powder fractions, the latter being the one that presented higher PAHs concentration. This may be due to the products generated in the pyrolysis of wood, used in the drying process of “yerba mate.” If powder were removed, a reduction of ∼3.5% of ∑PAHs and 6.5% of TEQ would be achieved. Although eliminating powder could be a strategy to reduce PAHs contamination, this would not be enough to diminish PAHs levels below the regulatory limits.